Anterior Lumbar Interbody Fusion With Cage Retrieval for the Treatment of Pseudarthrosis After Transforaminal Lumbar Interbody Fusion: A Single-Institution Case Series. Issue 2 (9th October 2020) - Safaee, Michael M; Tenorio, Alexander; Haddad, Alexander F; Wu, Bian; Hu, Serena S; Tay, Bobby; Burch, Shane; Berven, Sigurd H; Deviren, Vedat; Dhall, Sanjay S; Chou, Dean; Mummaneni, Praveen V; et al.
Abstract: BACKGROUND: The treatment of pseudarthrosis after transforaminal lumbar interbody fusion (TLIF) can be challenging, particularly when anterior column reconstruction is required. There are limited data on TLIF cage removal through an anterior approach. OBJECTIVE: To assess the safety and efficacy of anterior lumbar interbody fusion (ALIF) as a treatment for pseudarthrosis after TLIF. METHODS: ALIFs performed at a single academic medical center were reviewed to identify cases performed for the treatment of pseudarthrosis after TLIF. Patient demographics, surgical characteristics, perioperative complications, and 1-yr radiographic data were collected. RESULTS: A total of 84 patients were identified with mean age of 59 yr and 37 women (44.0%). A total of 16 patients (19.0%) underwent removal of 2 interbody cages for a total of 99 implants removed with distribution as follows: 1 L2/3 (0.9%), 6 L3/4 (5.7%), 37 L4/5 (41.5%), and 55 L5/S1 (51.9%). There were 2 intraoperative venous injuries (2.4%) and postoperative complications were as follows: 7 ileus (8.3%), 5 wound-related (6.0%), 1 rectus hematoma (1.1%), and 12 medical complications (14.3%), including 6 pulmonary (7.1%), 3 cardiac (3.6%), and 6 urinary tract infections (7.1%). Among 58 patients with at least 1-yr follow-up, 56 (96.6%) had solid fusion. There were 5 cases of subsidence (6.0%), none of which required surgical revision. Two patients (2.4%) required additional surgery at the level of ALIF for pseudarthrosis. CONCLUSION: ALIF is a safe and effective technique for the treatment of TLIF cage pseudarthrosis with a favorable risk profile.